2018
DOI: 10.1002/ejoc.201701710
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Highly Efficient Method for the Synthesis of Benzofulvenes via CsOH‐Catalyzed Condensation of Indene and Aldehydes

Abstract: A fast condensation of indene with a wide range of aldehydes catalyzed by cesium hydroxide monohydrate (CsOH·H2O) for the synthesis of benzofulvenes with good to excellent yields was demonstrated. The condensation can be completed within a few minutes under room temperature and air atmosphere without the use of special ligands or phase‐transfer catalysts. In addition, the ratio of indene to aldehydes played an important role in this reaction. The single condensation products 3 can be obtained as main products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To investigate this unusual reaction mechanism, we focused on the first step of oxygenation and considered three possible steps: SET, [21] HAT, [22] and deprotonation steps; [23] thus, the substrate parameters ionization energy (IE), bond dissociation energy (BDE), and p K a , corresponding to each mechanism, were compared with the substrate scope results (Table 1). Typical oxygenations of alkylarenes start from SET or HAT of alkylarenes, and the reactivities were related to IE or BDE [20–22] .…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this unusual reaction mechanism, we focused on the first step of oxygenation and considered three possible steps: SET, [21] HAT, [22] and deprotonation steps; [23] thus, the substrate parameters ionization energy (IE), bond dissociation energy (BDE), and p K a , corresponding to each mechanism, were compared with the substrate scope results (Table 1). Typical oxygenations of alkylarenes start from SET or HAT of alkylarenes, and the reactivities were related to IE or BDE [20–22] .…”
Section: Resultsmentioning
confidence: 99%
“…Manganese­(III) acetate dihydrate (97%) and TBHP (5.0–6.0 M) in decane solution were purchased from Sigma-Aldrich. Starting materials 1 , 4 , 6 , and 8 were prepared by the reported method. All the solvents used were of dry grade. The column chromatographic separations were performed over 100–200 mesh size silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…Data for 9-benzylidene-9 H -fluorene ( 6a ): 1 H NMR (400 MHz, CDCl 3 ): δ 7.82–7.78 (m, 1H), 7.74–7.71 (m, 3H), 7.57 (dd, J = 14.7, 7.7 Hz, 3H), 7.49–7.45 (m, 2H), 7.42–7.29 (m, 4H), (td, J = 7.7, 1.0 Hz, 1H). 13 C­{ 1 H} NMR (100 MHz, CDCl 3 ): δ 141.5, 139.4, 137.2, 136.4, 135.9, 131.9, 131.1, 128.9, 128.6, 127.2, 126.9, 126.8, 125.8, 124.5, 120.4, 120.0, 120.0, 119.8.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, various studies have demonstrated that these features of PIns can be improved by blending or forming copolymers with coumarone, vinyl monomers, methylindene, pyrrole, styrenes, ethylene, polyoxomethylene, and others; or composites with Montmorillonite . In both PIns and indene‐based co‐polymers and composites, the different reactivity of atoms at indenyl groups and, therefore, the distinct indenyl coupling routes remarkably affect the indene spatial orientations and/or polymer structures and properties . These indenyl coupling routes depend on the preparation method and reaction conditions, so their study becomes of paramount importance.…”
Section: Introductionmentioning
confidence: 99%